An efficient synthesis of 2,4,7-trisubstituted pyrimido[1,2-a][1,3,5]triazin-6-ones - Sachdeva, N.; Dolzhenko, Anton; Lim, S.; Ong, W.; Chui, W. (Royal Society of Chemistry, 2015)
© 2015 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique. A method for the preparation of novel pyrimido[1,2-a][1,3,5]triazin-6-one derivatives functionalized in positions 2, 4, and 7 of the ring was developed. Diversity in the derivatization of the pyrimido[1,2-a][1,3,5]triazin-6-one scaffold was successfully achieved by the introduction of substituents into positions 2 and 7 via two complementary approaches for the synthesis of key intermediates viz. pyrimidinylguanidines. Variations in position 4 of the pyrimido[1,2-a][1,3,5]triazine ring were made available by the regioselective introduction of various substituents via the triazine ring closure with corresponding aldehydes. The scope of the method was illustrated by the preparation of a library of 66 pyrimido[1,2-a][1,3,5]triazin-6-ones, which was demonstrated to be a source for new selective anticancer agents. Tautomeric preferences and anticancer properties were also explored for the prepared compounds.